The difference of mean waiting times between two classes of customers in a single-server FIFO queue: An experimental study - Romero-Silva, Rodrigo; Hurtado-Hernandez, Margarita (My University, 2017)
Previous studies have shown that the distribution of mean waiting times of different classes of customers is different for each class in a GI/G/1 queue with FIFO discipline. This experimental simulation study is motivated by those results as it investigates which are the conditions causing a difference of mean waiting times between two classes of customers using a FIFO discipline. Results from the study show that having a difference in the squared coefficient of variation of inter-arrival times between classes is the most important factor to determine whether a difference of mean waiting times between two classes exists. Furthermore, if a difference of mean service times between the two classes exists, the class with the highest mean service time will tend to have the smallest mean waiting time between the two classes, resulting in an unfair policy.